Informal Norms, Communication Spaces, and Work Environment Inclusiveness - Yani Fathur Rohman (Soshum: Jurnal Sosial dan Humaniora, 2020)
Protection of disability rights in the workplace is not adequate by applying formal rules made by the government, but needs to be strengthened by various informal mechanisms. Since 2016, Indonesian government has laws on persons with disabilities including the fulfillment of rights and protection of work. The fact, the government still faces various challenges in its implementation. Previous studies related to persons with disabilities and work environment highlighted three things including the government's affirmative policy towards persons with disabilities, the constraints of companies employing disabilities, as well as the impact of persons with disabilities on workforce diversity. This research exmines the interrelation of informal norms as a component in supporting existing formal rules and their impact on inclusiveness in the work environment. Qualitative methods are used and data collection is obtained through observation, documents, and in-depth interview. As a result, the strengthening of informal norms in the company is capable to eliminate social exclusion, especially related to infrastructures and facilities that are not yet accessible for employment with disabilities.